Pengetahuan dan Kesadaran Zakat; Implikasinya Terhadap Minat Karyawan Usaha Menengah Besar (UMB) untuk Membayar Zakat Pada BAZNAS - Najmudin, Najmudin; Ahyakudin, Ahyakudin; Pardiansyah, Elif; Sujai, Sujai; Maelani, Puspita; Sari, Rasidah Novita (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine (1). The effect of zakat knowledge on interest in paying zakat at BAZNAS. (2. Effect of zakat awareness on interest in paying zakat at BAZNAS. And (3). Effect of knowledge and understanding of zakat on interest in paying zakat at BAZNAS. The object of this research is employees of Large and Medium Enterprises (UMB) in Banten Province. The research method used is a quantitative-descriptive method. The data collection method uses a questionnaire. The data is processed using SPSS software version 23. The data analysis uses multiple linear regression methods. The results of this study indicate that (1) Zakat knowledge has a significant positive effect on the intention to pay zakat at BAZNAS. (2 Awareness of zakat on interest in paying zakat at BAZNAS. And (3). Knowledge and awareness of zakat simultaneously significantly positively affect interest in paying zakat on BAZNAS. Interest in paying zakat at BAZNAS Banten Province is influenced by the knowledge and understanding of zakat employees by 48.3 percent. In comparison, the remaining 51.7 percent is influenced by other variables not examined in this study.